2019
DOI: 10.1038/s41385-018-0126-0
|View full text |Cite|
|
Sign up to set email alerts
|

Two distinct colonic CD14+ subsets characterized by single-cell RNA profiling in Crohn's disease

Abstract: Inflammatory bowel diseases are associated with dysregulated immune responses in the intestinal tissue. Four molecularly identified macrophage subsets control immune homeostasis in healthy gut. However, the specific roles and transcriptomic profiles of the phenotypically heterogeneous CD14 + macrophage-like population in inflamed gut remain to be investigated in Crohn's disease (CD). Here we identified two phenotypically, morphologically and functionally distinct colonic HLADR + SIRPα + CD14 + subpopulations t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
83
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(88 citation statements)
references
References 81 publications
(117 reference statements)
4
83
1
Order By: Relevance
“…It is now clear that the frequency and number of Mfs among intestinal LP cells is increased in IBD patients compared to controls, especially in active lesion areas (132,221,223,225,226,228,246,263,(267)(268)(269)(270)(271)(272) (Figure 5E). More specifically, the augmentation of intestinal Mfs is due to an increase in the frequency of immature Mfs among LP cells, despite that somewhat different surface markers and combinations thereof have been used to characterized them (i.e., HLA-DR or CD11c levels; scRNA-seq) (132,221,223,225,226,228,256,263,270,(272)(273)(274)(275) (Figure 5F). This accumulation seems to be due to the inflammatory intestinal microenvironment of IBD patients, which boosts the recruitment of classical monocytes through mechanisms involving CCL2, IL-8, and TGF-β signaling (223,276).…”
Section: Phenotype and Frequency Of Intestinal Mucosa Macrophagesmentioning
confidence: 95%
See 3 more Smart Citations
“…It is now clear that the frequency and number of Mfs among intestinal LP cells is increased in IBD patients compared to controls, especially in active lesion areas (132,221,223,225,226,228,246,263,(267)(268)(269)(270)(271)(272) (Figure 5E). More specifically, the augmentation of intestinal Mfs is due to an increase in the frequency of immature Mfs among LP cells, despite that somewhat different surface markers and combinations thereof have been used to characterized them (i.e., HLA-DR or CD11c levels; scRNA-seq) (132,221,223,225,226,228,256,263,270,(272)(273)(274)(275) (Figure 5F). This accumulation seems to be due to the inflammatory intestinal microenvironment of IBD patients, which boosts the recruitment of classical monocytes through mechanisms involving CCL2, IL-8, and TGF-β signaling (223,276).…”
Section: Phenotype and Frequency Of Intestinal Mucosa Macrophagesmentioning
confidence: 95%
“…These newly recruited monocytes are maintained in the immature pro-inflammatory state, which in turn amplify intestinal chronic inflammation (11,277). Chapuy et al showed that the frequency of immature Mfs, but not mature Mfs, is positively correlated with endoscopic score of disease severity in Crohn's patients (228). To note, age, gender, age at diagnosis, disease location and disease behavior, as well treatment history, did not influence the increased frequency of immature Mfs in Crohn's patients (228).…”
Section: Phenotype and Frequency Of Intestinal Mucosa Macrophagesmentioning
confidence: 99%
See 2 more Smart Citations
“…Single-cell transcriptomic technologies have enabled the exciting discovery of novel cell populations within various in vivo contexts (Baron et al, 2016;Chapuy et al, 2019;Jia et al, 2018;Kernfeld et al, 2018;Kurtulus et al, 2019;Paul et al, 2015;Satija et al, 2015;Shekhar et al, 2016;Singer et al, 2016;Spallanzani et al, 2019;Vento-Tormo et al, 2018;Villani et al, 2017). Following the discovery of a new cell population of interest based on full transcriptome analysis (of typically a few thousand genes), follow-up studies require succinct gene-marker panels by which the cells of interest can be distinguished from the general cell population ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%